PERLINDUNGAN HUKUM TERHADAP PENCIPTA LAGU “LAGI SYANTIK” ATAS PERUBAHAN LIRIK TANPA IZIN PEMEGANG HAK CIPTA - Lully Tiyas Junita (Yurispruden: Jurnal Fakultas Hukum Universitas Islam Malang, 2021)
Copyright is an exclusive right that arises automatically based on declarative principles after the creation is in real or visualized form. Legal protection for songwriters is regulated in Law Number 28 of 2014 concerning Copyright. This research covers two main problems. First one, how is the implementation of copyright infringement on the song "Lagi Syantik" which is sung without permission from the copyright holder? The second, how is the legal protection of authors for songs whose lyrics have been changed without the permission of the copyright holders? This paper uses normative juridical research. This research uses 2 types of approaches, such as the statute approach and the case approach. The result of the research were the cover version of the song is not a prohibited activity if it is carried out based on applicable legal regulations and legal protection for copyright holders is regulated in the Copyright Law, Criminal Law, and Civil Law.